Optimization of variable-direction long-range trajectory for the unpowered flight vehicle - Pham, Tuan Hung; Nguyen, Duc Cuong (Vietnam Journal of Science and Technology, 2025)
The study presents a new problem of trajectory for unpowered flight vehicles. The research object includes fixed-wing unpowered flight vehicles operating in the range of transonic and subsonic speeds. The purpose is to find the maximum range when unpowered flight vehicles have to perform the trajectory with direction change. In this study, the flight direction angle at the initial point of the trajectory is a right angle to the target line and the angle at the final point is also a right angle but in an opposite direction. The research focuses on considering the trajectory optimization problem in the horizontal plane according to the criterion of maximum range. It is known that a maximum range of a hundred kilometers can be achieved by fixed-wing unpowered flight vehicles when dropped from an altitude of about ten kilometers at transonic speeds to the target directly. Based on a trajectory scheme and conditions of the trajectory in the vertical plane, this study has optimized the trajectory with direction changes in the horizontal plane. The result obtained is a maximum range of about eighty kilometers. Although this range may be shorter than the previous study by ten kilometers, it opens up new potential applications for fixed-wing unpowered flight vehicles such as their capability for long-range multiple trajectories.